Teaching Controversial Issues in a Populist and Post-Truth Context - Stitzlein, Sarah (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2024)
Many teachers and education scholars are quick to endorse discussing controversial issues in classrooms, especially in the context of “divisive concept” legislation that proposes bans or limitations on how contentious matters are taught in schools. This approach, however, may not be the best choice in a post-truth and populist setting that challenges the values of liberal democracy and the norms of discussion that are endorsed in deliberative democracy. Rather than recommending doubling down on traditional approaches in this new context, this article proposes a form of pragmatist inquiry as a better pedagogical method. Pragmatist inquiry shares some tenets with aspects of populism and post-truth, yet heads off some of their worst tendencies. It offers a more suitable pedagogical approach than the liberal democracy approaches more closely aligned with typical classroom discussion and related forms of deliberation and debate.